Interpretation Problems of the Legal Norms of Municipal Companies in Poland - Bielińska-Dusza, Edyta; Suchowińska, Ewa; Synowiec, Małgorzata (Journal of Public Governance, 2023)
Objective: The article addresses the problem related to the interpretation of legal norms on the functioning of municipal companies, filling the research gap resulting from the paucity of literature and scientific research on the interpretative difficulties as well as the lack of clear-cut solutions on this issue. The problems that have arisen in connection with the free interpretation of legal norms on the functioning of municipal companies indicate the necessity of isolating a legal definition of a municipal company in the legal system and defining separate and unified legal norms for this entity. This would often avoid contradictory interpretations of the law or interpretation of the law according to the principle of “good practice”. The objective is to indicate the need to create a dedicated legal standard(s) for municipal companies (particularly with a majority share of local government units).Research Design & Methods: In the course of the research process, various methods were used, including analysis of the literature review, the method of analysis, synthesis, and deduction, as well as legal acts and data on the activities of selected municipal companies.Findings: The lack of a uniform (sanctioned by detailed, systemic legal regulations) model of a municipal company translates into numerous interpretation problems in applying legal acts dedicated to this legal form. This results in ineffective corporate governance and numerous irregularities in the functioning and exercise of control by local governments, courts, and provincial offices (supervision by the Governor) over companies with local government participation.Implications/Recommendations: The guidelines about municipal companies should delineate the issues currently addressed across various legislative enactments, incorporating oversight and regulation of utilising public funds. Moreover, this shall contribute to ensuring the judicious conduct of financial operations in conformity with legal standards.Contribution/Value Added: The suggested definition sets out clear criteria for identifying entities with hybrid public and private management characteristics involved in public utility tasks. Additionally, the proposal emphasises considering social and economic factors, using specialised indicators to assess municipal company performance, and underscores the need to articulate their roles precisely within legal frameworks and in fulfilling socioeconomic missions.